2024
DOI: 10.3390/pathogens13020155
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans Cytolethal Distending Toxin Induces Cellugyrin-(Synaptogyrin 2) Dependent Cellular Senescence in Oral Keratinocytes

Bruce J. Shenker,
Jonathan Korostoff,
Lisa P. Walker
et al.

Abstract: Recently, we reported that oral-epithelial cells (OE) are unique in their response to Aggregatibacter actinomycetemcomitans cytolethal distending toxin (Cdt) in that cell cycle arrest (G2/M) occurs without leading to apoptosis. We now demonstrate that Cdt-induced cell cycle arrest in OE has a duration of at least 7 days with no change in viability. Moreover, toxin-treated OE develops a new phenotype consistent with cellular senescence; this includes increased senescence-associated β-galactosidase (SA-β-gal) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Recently, we determined that cellugyrin plays a requisite role in the internalization and endosomal trafficking of Cdts ( Boesze-Battaglia et al., 2016 ; Boesze-Battaglia et al., 2017 ; Boesze-Battaglia et al., 2020 ). To date, we have demonstrated that cellugyrin expression in human lymphocytes, macrophages and, more recently, oral keratinocytes is required for toxin entry and subsequent intoxication of these cells ( Boesze-Battaglia et al., 2016 ; Boesze-Battaglia et al., 2017 ; Boesze-Battaglia et al., 2020 ; Shenker et al, 2024 ). Cdts are produced by more than 30 γ- and ϵ-Proteobacteria; indeed, we have shown that cellugyrin is required for at least three Cdts produced by Aggregatibacter actinomycetemcomitans ( Aa Cdt), Haemophilus ducreyi ( Hd Cdt) and Campylobacter jejuni ( Cj Cdt) ( Boesze-Battaglia et al., 2017 ; Boesze-Battaglia et al., 2020 ; Huang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we determined that cellugyrin plays a requisite role in the internalization and endosomal trafficking of Cdts ( Boesze-Battaglia et al., 2016 ; Boesze-Battaglia et al., 2017 ; Boesze-Battaglia et al., 2020 ). To date, we have demonstrated that cellugyrin expression in human lymphocytes, macrophages and, more recently, oral keratinocytes is required for toxin entry and subsequent intoxication of these cells ( Boesze-Battaglia et al., 2016 ; Boesze-Battaglia et al., 2017 ; Boesze-Battaglia et al., 2020 ; Shenker et al, 2024 ). Cdts are produced by more than 30 γ- and ϵ-Proteobacteria; indeed, we have shown that cellugyrin is required for at least three Cdts produced by Aggregatibacter actinomycetemcomitans ( Aa Cdt), Haemophilus ducreyi ( Hd Cdt) and Campylobacter jejuni ( Cj Cdt) ( Boesze-Battaglia et al., 2017 ; Boesze-Battaglia et al., 2020 ; Huang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%